2005
DOI: 10.1029/2005jb003826
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric and oceanic contributions to Chandler wobble excitation determined by wavelet filtering

Abstract: [1] Fluctuations of Earth rotation are associated with the redistribution and motion of mass elements in the Earth system. On seasonal to interannual timescales, the largest effects are due to mass redistributions within atmosphere and oceans. In order to study the Earth's reaction on geophysical excitations, the dynamic Earth system model DyMEG has been developed. It is based on the balance of angular momentum in the Earth system. The model is forced by consistent atmospheric and oceanic angular momenta from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 29 publications
(53 reference statements)
1
28
0
2
Order By: Relevance
“…DyMEG allows for the consideration and superposition of various effects which makes the model an ideal tool for the forward simulation and analysis of ERP. It has been shown in several studies that the results of DyMEG agree well with observed ERP on timescales from days to several years [e.g., Seitz and Schmidt, 2005].…”
Section: Dynamic Earth System Model Dymegsupporting
confidence: 65%
See 2 more Smart Citations
“…DyMEG allows for the consideration and superposition of various effects which makes the model an ideal tool for the forward simulation and analysis of ERP. It has been shown in several studies that the results of DyMEG agree well with observed ERP on timescales from days to several years [e.g., Seitz and Schmidt, 2005].…”
Section: Dynamic Earth System Model Dymegsupporting
confidence: 65%
“…The annual oscillation is predominantly induced by geophysical processes in the Earth system. The Chandler oscillation is a free rotational mode of the Earth, originating from the misalignment of the polar [Seitz and Schmidt, 2005] of observations provided by the IERS in its C01 and C04 series [Dick and Richter, 2009]. While the annual signal is rather uniform, the Chandler oscillation features strong amplitude variations.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Following Aoyama et al (2003), atmospheric and ocean-bottom pressure and winds are comparable sources of excitation, intermittently playing a prominent role. Seitz & Schmidt (2005) conclude that the atmospheric and oceanic bottom pressure fluctuations are the prominent cause of the CW variability. They could account for some features in the band of 400-460 days by wavelet analysis: an amplitude increase between 1980 and 1990 and a decrease after 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that the CW is highly variable with respect to its amplitude (e.g., Carter, 1981Carter, , 1982Höpfner, 2003;Chen et al, 2009Chen et al, , 2013a, some have considered it to have double or multiple frequencies (e.g., Chao, 1983;Pan, 2012), and some have considered its frequency to be invariant (e.g., Okubo, 1982;Vicente and Wilson, 1997;Gross et al, 2003;Seitz and Schmidt, 2005). If the CW is frequency modulated as Carter (1981Carter ( , 1982 suggested, namely, the frequency is governed by the magnitude, it will create an infinite number of sidebands, arranged symmetrically about the carrier and spaced at integer multiples of the modulating frequency (Carter, 1981).…”
Section: Introductionmentioning
confidence: 99%